2011
DOI: 10.1590/s2176-94512011000100014
|View full text |Cite
|
Sign up to set email alerts
|

Análise da posição rotacional do primeiro molar permanente superior na má oclusão de Classe II Divisão 1

Abstract: OBJETIVO: comparar a posição rotacional do primeiro molar permanente superior entre a oclusão normal e a má oclusão de Classe II, Divisão 1, de Angle. MÉTODOS: a amostra de oclusão normal consistiu de 60 pares de modelos de pacientes com média de idade de 15,1 anos, denominada Grupo 1. A amostra de Classe II, Divisão 1, consistiu de 120 pares de modelos de gesso de pacientes não tratados, com média de idade de 15,5 anos, denominada Grupo 2. Os modelos superiores foram escaneados e a posição dos molares superio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
(20 reference statements)
3
2
1
Order By: Relevance
“…The mean angle of Friel was 58.25°, which is similar to the values reported by Giuntini et al [19] and Junqueira et al [16] (55.8° and 57.45°, resp.). Kanomi et al [20] found a higher value for this indicator (63.5°), probably because their population comprised several malocclusion types and not Class II division 1 malocclusion alone.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The mean angle of Friel was 58.25°, which is similar to the values reported by Giuntini et al [19] and Junqueira et al [16] (55.8° and 57.45°, resp.). Kanomi et al [20] found a higher value for this indicator (63.5°), probably because their population comprised several malocclusion types and not Class II division 1 malocclusion alone.…”
Section: Discussionsupporting
confidence: 90%
“…It is noteworthy that the mean values of indicators 1 and 2 are very similar to those obtained in other studies [5, 16] of Class II malocclusion using a similar methodology. The small differences observed may result from other factors in addition to the malocclusion type that also causes rotation of the first molars, such as the upper arch morphology, changes in the shape and size of the maxillary first molars, canines, and premolars, malpositioning of the canines and premolars, the presence or absence of interproximal caries, and early loss of the deciduous molars.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations